The Influence of Service Quality and Price on Repurchase Intention at Mumu Kopi in Padang City - Salsabil Haura; Kurnia Illahi Manvi (Journal of Multidimensional Management, 2025)
This study explores the impact of service quality and pricing on customers' repurchase intention at Mumu Kopi, a coffee shop located in Padang City. The research was prompted by a noticeable decline in customer visits, which is believed to be linked to service shortcomings and increasing prices. Utilizing a quantitative approach with a causal-associative method, data were collected through questionnaires distributed to 100 participants selected using an accidental sampling technique. The analysis was conducted using multiple linear regression with the aid of SPSS version 25. The findings reveal that both service quality and price exert a positive and statistically significant influence on repurchase intention. Service quality demonstrated a beta coefficient of 0.639 with a significance level of 0.000, indicating a strong effect. Meanwhile, price showed a beta coefficient of 0.219 with a significance level of 0.007. The F-test result (F = 42.456, p = 0.000) confirms the combined effect of both variables on repurchase behavior. Furthermore, the coefficient of determination (R²) was 0.467, suggesting that 46.7% of the variation in repurchase intention is explained by the two variables, while the remaining 53.3% may be attributed to other unmeasured factors. These results highlight the necessity of improving service standards and implementing effective pricing strategies to foster customer loyalty and encourage repeat purchases—critical components for sustaining competitiveness in the coffee shop industry.